Immigration ensures population survival in the Siberian flying squirrel. Issue 6 (15th February 2017) - Brommer, Jon E.; Wistbacka, Ralf; Selonen, Vesa
Abstract: Linking dispersal to population growth remains a challenging task and is a major knowledge gap, for example, for conservation management. We studied relative roles of different demographic rates behind population growth in Siberian flying squirrels in two nest‐box breeding populations in western Finland. Adults and offspring were captured and individually identifiable. We constructed an integrated population model, which estimated all relevant annual demographic rates (birth, local [apparent] survival, and immigration) as well as population growth rates. One population (studied 2002–2014) fluctuated around a steady‐state equilibrium, whereas the other (studied 1995–2014) showed a numerical decline. Immigration was the demographic rate which showed clear correlations to annual population growth rates in both populations. Population growth rate was density dependent in both populations. None of the demographic rates nor the population growth rate correlated across the two study populations, despite their proximity suggesting that factors regulating the dynamics are determined locally. We conclude that flying squirrels may persist in a network of uncoupled subpopulations, where movement between subpopulations is of critical importance. Our study supports the view that dispersal has the key role in population survival of a small forest rodent. Abstract : Which demographic rate (reproduction, survival, emi‐, or immigration) determines growth of a population is a critical question in conservation biology. This is, however, also a pervasive question especially because identifying immigration is not trivial in wild populations. We here use a state‐of‐the‐art approach to estimate the association between all demographic rates and annual growth in two flying squirrel populations to show that population persistence is critically dependent on immigrants.